La tombe comme isthme (barzakh) entre les vivants et les morts : points de vue croisés du soufisme et du shī‘isme imāmite (al-Ghazālī et al-Fayḍ al-Kāshānī) - Mathieu Terrier (Université de Provence, 2019)
Visiting the tombs and meditating on the afterlife occupy an important place in religious life and theological thinking in Islam, whether in – predominantly Sunni – Sufism or in Imāmi Shī‘ism. This is shown by some chapters of al- Ghazālī’s (d. 505/1111) Iḥyā’ ‘ulūm al-dīn and al-Fayḍ al-Kāshānī’s (d. 1091/1680) al-Maḥajja al-bayḍā, a revision of the former from a Shī‘i perspective. In both works, the tomb appears as a source of meditation and moral edification for the living, and for the dead, as a first station of the final destiny, i.e. the place of the “lesser resurrection”. The theme of the tomb is thus at the crossroads of ethics and eschatology, that is, a normative discourse on life in this world and a visionary discourse on the afterlife, two approaches particularly developed in Sufism, Shī‘ism as well as Islamic philosophy. Seen as an isthmus or interface between the living and the dead, the tomb also stands out as a place where the spiritual currents of Islam come closer together.